Anti-quorum Sensing Activities of Selected Coral Symbiotic Bacterial Extracts From the South China Sea - Ma, Zhi-Ping; Song, Yu; Cai, Zhong-Hua; Lin, Zhi-Jun; Lin, Guang-Hui; Wang, Yan; Zhou, Jin (Frontiers in Cellular and Infection Microbiology, 2018)
The worldwide increase in antibiotic-resistant pathogens means that identification of alternative antibacterial drug targets and the subsequent development of new treatment strategies are urgently required. One such new target is the quorum sensing (QS) system. Coral microbial consortia harbor an enormous diversity of microbes, and are thus rich sources for isolating novel bioactive and pharmacologically valuable natural products. However, to date, the versatility of their bioactive compounds has not been broadly explored. In this study, about two hundred bacterial colonies were isolated from a coral species (Pocillopora damicornis) and screened for their ability to inhibit QS using the bioreporter strain Chromobacterium violaceum ATCC 12472. Approximately 15% (30 isolates) exhibited anti-QS activity, against the indicator strain. Among them, a typical Gram-positive bacterium, D11 (Staphylococcus hominis) was identified and its anti-QS activity was investigated. Confocal microscopy observations showed that the bacterial extract inhibited the biofilm formation of clinical isolates of wild-type P. aeruginosa PAO1 in a dose-dependent pattern. Chromatographic separation led to the isolation of a potent QS inhibitor that was identified by high-performance liquid chromatography-mass spectrometry (HPLC-MS) and nuclear magnetic resonance (NMR) spectroscopy as DL-homocysteine thiolactone. Gene expression analyses using RT-PCR showed that strain D11 led to a significant down-regulation of QS regulatory genes (lasI, lasR, rhlI, and rhlR), as well as a virulence-related gene (lasB). From the chemical structure, the target compound (DL-homocysteine thiolactone) is an analog of the acyl-homoserine lactones (AHLs), and we presume that DL-homocysteine thiolactone outcompetes AHL in occupying the receptor and thereby inhibiting QS. Whole-genome sequence analysis of S. hominis D11 revealed the presence of predicted genes involved in the biosynthesis of homocysteine thiolactone. This study indicates that coral microbes are a resource bank for developing QS inhibitors and they will facilitate the discovery of new biotechnologically relevant compounds that could be used instead of traditional antibiotics.